Prokineticin 2 via Calcium-Sensing Receptor Activated NLRP3 Inflammasome Pathway in the Testicular Macrophages of Uropathogenic Escherichia coli-Induced Orchitis - Su, Yufang; Zhang, Yuan; Hu, Zhiyong; He, Liting; Wang, Wei; Xu, Jia; Fan, Zunpan; Liu, Chunyan; Zhang, Huiping; Zhao, Kai (Frontiers in Immunology, 2020)
Reproductive tract infections contribute to the development of testicular inflammatory lesions, leading to male infertility. Previous research shows that the activation of the NLRP3 inflammasome in orchitis promotes the secretion and maturation of IL-1β and thus decreases male fertility. The calcium-sensing receptor (CaSR) is a calcium-sensitive receptor and closely related to the secretion of proinflammatory cytokines. Increase in CaSR level promotes the assembly and activation of the NLRP3 inflammasome. However, the role of calcium-sensitive receptors in orchitis is unknown. We first constructed a uropathogenic Escherichia Coli (UPEC) rat orchitis model, then detected the expression of CaSR and NLRP3 inflammatory pathway protein in TM through RT-PCR and WB, calcium levels in testicular macrophages (TM) through flow cytometry, and proinflammatory factor IL-1β through ELISA. In addition, testosterone levels in the serum samples waere detected using liquid chromatography-mass spectrometry (LC-MS). Here, we showed that CaSR upregulation after infection in TM in a rat model of UPEC induces the activation of the NLRP3 inflammasome pathway and thereby enhances IL-1β secretion and reduces testosterone level in the blood. Moreover, CaSR inhibitors can alleviate inflammatory impairment. After UPEC challenge in vitro, CaSR promoted NLRP3 expression and released IL-1β cleaved from TM into the supernatant. Overall, elevated CaSR levels in TM in testes with UPEC-induced orchitis may impair testosterone synthesis through the activation of the NLRP3 pathway and PK2 is an upstream regulatory protein of CaSR. Our research further showed the underlying mechanisms of inflammation-related male infertility and provides anti-inflammatory therapeutic targets for male infertility.